A Review: Benefit of Pereskia bleo (Kunth) DC Leaves - Natasya Hermawan; Sephira Odelia; Lisa Angereni; Leonid Fornaris Castro (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background of study: Pereskia bleo (Kunth) DC, commonly known as Daun tujuh jarum, is a leafy cactus traditionally used in South America, Southeast Asia, and other tropical regions for treating various ailments, including cancer, diabetes, hypertension, ulcers, inflammation, and rheumatism. Its leaves are commonly consumed raw, boiled, or prepared as tea and juice. In recent years, scientific interest in P. bleo has increased due to its rich antioxidant content, diverse phytochemicals, and promising therapeutic potential. Studies have identified proteins, essential amino acids, flavonoids, alkaloids, sterols, and phenolic compounds that may contribute to its health benefits.Aims and scope of paper: This review aims to summarize the traditional uses, nutritional value, phytochemical composition, and pharmacological activities of Pereskia bleo leaves, with particular emphasis on their antioxidant and medicinal properties. Applications in food, health, and traditional medicine are discussed, along with potential safety concerns.Methods: A literature-based approach was employed, drawing on ethnopharmacological surveys, phytochemical investigations, and pharmacological studies to evaluate the properties and biological effects of the plant.Result: The findings indicate that P. bleo leaves possess antioxidant, anticancer, antimicrobial, and anti-inflammatory activities. Several studies report strong cytotoxic effects against cancer cell lines, high nutritional value, and low toxicity in animal models, with only mild adverse effects documented in humans.Conclusion: Pereskia bleo demonstrates considerable potential as a natural antioxidant, antimicrobial, and anticancer agent. Although generally considered safe, its use should be approached with caution due to possible herb–drug interactions, and further clinical studies are required to confirm its efficacy and safety